Prevalence of nursing diagnoses in the immediate post-operative c-esarean system in the post-anesthetic recovery unit (Research, Society and Development, 2023)
Introduction: The gestational process is characterized by several physical, psychological, emotional and social changes in a woman's life. Nurses have the role of identifying potential risks, tracing nursing diagnoses (ND) and planning their care, disseminating good health practices in all obstetric scenarios. Objectives: To identify nursing diagnoses in puerperal women during the period of hospitalization in the post-anesthesia care unit (PACU) undergoing cesarean section. Methods: This is an observational, exploratory-descriptive study with a quantitative approach. The sample consisted of 47 pregnant women who opted for cesarean delivery, aged ≥ 18 years and SUS users. Results: Of the 47 women evaluated, the mean age was 30.1 ± 6.2 years, non-white (74.5%; n=35), married (55.3%; n=26), with 12 years or more of study (42.6%; n=20), perform paid activities (61%; n=29) and live in cities surrounding Campina Grande (59.6%; n=28). Of the 12 ND listed, nine were evidenced in the study, four of which were more prevalent, such as anxiety (55.3%; n=26), nausea (38.3%; n=18), hypothermia (27.7%; n =13) and risk for aspiration (14.9%; n=7). In all ND, nursing assistance was provided for their resolution. Conclusion: Anxiety, nausea, hypothermia and risk of aspiration were the most prevalent diagnoses in the present study. Nursing care in the PACU helps to reduce the occurrence of postpartum complications. However, it can be inferred that failures occur in the previous stages of care, with the need for greater control of the pregnant woman's emotional state.